Parents our most important resource - Woronko, Ula; Shapiro, Leah; Magna Systems, Inc.; General Learning Communications (Illinois : Magna Systems Inc., 2004)
Early Childhood Programs throughout the country are becoming increasingly accountable for the progress that children are making in their care. This video series explores the value of authentic assessment in documanting young children's progress, observational methods used to assess young children, systems used to organize the data and different formal assessment instruments or checklists used to collate the data
Title from title screen
Educational consultant, Leah Shapiro ; camera/editor, Nick Kolias
Narrator: Rhoda Olenick
Keywords: Child, Preschool -- education -- United States; Educational Measurement -- United States; Child development -- United States; Curriculum -- United States